Unemployment Insurance Simulation Model (UISIM) - Fares, Jean (World Bank, Washington, DC, 2012)
This note describes the key features of the Unemployment Insurance Simulation Model (UISIM) - how the model is structured, what data inputs are needed, and what outputs the model generates (the model comes with user's and technical manuals, which provide detailed information about how to operate the model and how it calculates the outputs). For illustrative purposes, the note also presents an example where the model is used to generate simulations for a countrywide unemployment insurance (UI) system. The appendix to the note describes typical data sources and provides a detailed description of requisite data.